2022
DOI: 10.3390/jfb14010021
|View full text |Cite
|
Sign up to set email alerts
|

Updated Perspectives on Direct Vascular Cellular Reprogramming and Their Potential Applications in Tissue Engineered Vascular Grafts

Abstract: Cardiovascular disease is a globally prevalent disease with far-reaching medical and socio-economic consequences. Although improvements in treatment pathways and revascularisation therapies have slowed disease progression, contemporary management fails to modulate the underlying atherosclerotic process and sustainably replace damaged arterial tissue. Direct cellular reprogramming is a rapidly evolving and innovative tissue regenerative approach that holds promise to restore functional vasculature and restore b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Several studies have reported small colonies of progenitor cells found in various locations in the arterial wall, particularly in the adventitia. These progenitor cells include endothelial, smooth muscle and haematopoietic stem/progenitor cells [19,20]. The nodular image ventral to the abdominal aorta on CT scan 2020 may correspond to these small colonies of progenitor cells, which would be the start of the anastomosing haemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported small colonies of progenitor cells found in various locations in the arterial wall, particularly in the adventitia. These progenitor cells include endothelial, smooth muscle and haematopoietic stem/progenitor cells [19,20]. The nodular image ventral to the abdominal aorta on CT scan 2020 may correspond to these small colonies of progenitor cells, which would be the start of the anastomosing haemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing uniaxial stretch in 2D culture to a 3D construct, there is significantly higher increase in VSMC specific markers ACTA2 and calponin ( 160 ) suggesting that a 3D environment allows for more robust cell-cell and cell-matrix interactions. For this purpose, several 3D models ( 161 ) have been in development over the last several years that incorporate multiple cell types in a bio-degradable matrix. Some key formats include vascular organoids (VOs) ( 138 ), vessel on a chip microfluidic device (VoC) and bioink-based extrusion or bioprinting.…”
Section: Complex Three-dimensional Disease Modelsmentioning
confidence: 99%
“…Cardiovascular and orthopedic diseases are two global epidemic diseases with far-reaching medical and socio-economic consequences [ 7 ]. Understanding the mechanical characteristics of arterial walls, blood flow, and valves holds great importance for the diagnosis, management, and treatment of cardiovascular diseases [ 8 , 9 , 10 ].…”
mentioning
confidence: 99%